2020
DOI: 10.1093/aob/mcaa154
|View full text |Cite
|
Sign up to set email alerts
|

Fossil evidence from South America for the diversification of Cunoniaceae by the earliest Palaeocene

Abstract: Background and Aims Cunoniaceae are woody plants with a distribution that suggests a complex history of Gondwanan vicariance, long-distance dispersal, diversification, and extinction. Only four out of c. 27 genera in Cunoniaceae are native to South America today, but the discovery of extinct species from Argentine Patagonia is providing new information about the history of this family in South America Methods We describe foss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 72 publications
0
18
0
Order By: Relevance
“…Secondly, the Southern Cone of South America appears to have been another significant center of diversity for the Cunoniaceae, with fossils described from the Paleocene and Eocene of Argentina. These comprise two extinct genera, Lacinipetalum Jud, Gandolfo, Iglesias & Wilf (Jud et al, 2018 ) and Cunoniantha Jud & Gandolfo (Jud and Gandolfo, 2021 ), as well as an extinct species of Ceratopetalum (Gandolfo and Hermsen, 2017 ), a genus now composed of nine extant species in Australia and New Guinea. In addition, fossils from the Oligocene of Tasmania have been placed in the genera Acsmithia Hoogland (= Spiraeanthemum ), Callicoma , Schizomeria , and Vesselowskya , although these genera no longer occur on this island (Carpenter and Buchanan, 1993 ), and a fossil assigned to Codia was described from the middle Eocene to Oligocene of Western Australia (Barnes and Hill, 1999 ), although this genus is now confined to New Caledonia.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, the Southern Cone of South America appears to have been another significant center of diversity for the Cunoniaceae, with fossils described from the Paleocene and Eocene of Argentina. These comprise two extinct genera, Lacinipetalum Jud, Gandolfo, Iglesias & Wilf (Jud et al, 2018 ) and Cunoniantha Jud & Gandolfo (Jud and Gandolfo, 2021 ), as well as an extinct species of Ceratopetalum (Gandolfo and Hermsen, 2017 ), a genus now composed of nine extant species in Australia and New Guinea. In addition, fossils from the Oligocene of Tasmania have been placed in the genera Acsmithia Hoogland (= Spiraeanthemum ), Callicoma , Schizomeria , and Vesselowskya , although these genera no longer occur on this island (Carpenter and Buchanan, 1993 ), and a fossil assigned to Codia was described from the middle Eocene to Oligocene of Western Australia (Barnes and Hill, 1999 ), although this genus is now confined to New Caledonia.…”
Section: Discussionmentioning
confidence: 99%
“…or Cunonieae more broadly. It should be noted, however, that Jud and Gandolfo (2021) expressed reservations about the assignment of Cretaceous and Paleogene Weinmannioxylon wood to crown Cunoniaceae; furthermore, not all species of Weinmannioxylon are thought to be related to Weinmannia s.l. or other genera of Cunonieae (discussed further below).…”
Section: Discussionmentioning
confidence: 99%
“…Weinmannioxylon multiperforatum (the type species) and Weinmannioxylon pluriradiatum , also considered similar to wood of Weinmannia s.l. and Cunonia (Petriella, 1972; Brea et al, 2015), have been found at several Paleogene localities in Chubut and Neuquén provinces in Argentina (Petriella, 1972; Raigemborn et al, 2009; Brea et al, 2015; Jud and Gandolfo, 2021). One Neogene occurrence of wood from the Falkland (Malvinas) Islands has been assigned to cf.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations